Exploring the protective mechanisms of the yunpi jiedu tongluo qushi decoction on methotrexate-induced reproductive damage in male rats based on Nrf2/HO-1 signaling pathway - Chen, Wu; Chen, Min; Li, Dian-Ming; Shi, Wei-Man; Zhang, Min; Li, Zhi-Yu; Huang, Lin; Wen, Cheng-Ping; Wang, Qiao (Frontiers in Cell and Developmental Biology, 2025)
BackgroundMethotrexate (MTX), a folate antagonist, is widely used in the treatment of tumors and autoimmune diseases such as rheumatoid arthritis (RA), due to its antiproliferative, antimetabolic, and potent anti-inflammatory properties. However, high-dose or long-term use of MTX can result in toxicity to the gastrointestinal, hemopoietic, and reproductive tissues. Yunpi Jiedu Tongluo Qushi Decoction (YJT), an effective Chinese herbal formula, is utilized in RA treatment to mitigate the toxic and side effect of MTX. Despite its clinical application, the precise effects and the underlying mechanisms through which it mitigates reproductive damage have yet to be elucidated.PurposeThis study was conducted to investigate the protective effects and mechanisms of YJT against MTX-induced reproductive toxicity.MethodsHere we used an integrated approach combining Ultra Performance Liquid Chromatography-Mass Spectrometry (UPLC-MS), in vitro and vivo experiments, and molecular docking technology to systematically elucidate the protective effects and mechanism of YJT.ResultsWe identified nine active ingredients in YJT that contributed to its efficacy. YJT alleviated testicular damage in MTX-exposed rats, resolved abnormalities of sperm morphology, structure, and quality, decreased the number of TUNEL-positive cells in testicular tissue, and reduced oxidative stress (OS). YJT affected GC2spd cell apoptosis by regulating OS response. Both in vitro and vivo experiments showed that YJT can activate the Nrf2/HO-1 signaling pathway against OS response. Molecular docking results further confirmed the strong binding activity between the core components of YJT and Nrf2, HO-1.ConclusionCollectively, our findings indicate that YJT protects against MTX-induced apoptosis in spermatogenic cells by inhibiting OS and Nrf2/HO-1 signaling pathway. This study provides a theoretical foundation and experimental basis for the use of YJT to alleviate MTX-induced reproductive toxicity.